2012
DOI: 10.1177/0145445512445609
|View full text |Cite
|
Sign up to set email alerts
|

Improving Generalization of Peer Socialization Gains in Inclusive School Settings Using Initiations Training

Abstract: Social engagement by children with autism spectrum disorder (ASD) in unstructured school settings generally occurs at very low levels, if at all. Although many interventions improve peer socialization, generalization and maintenance of such gains when interventions are faded is typically low. The present study employed a multiple baseline design across participants to target generalization in the absence of interventionists in elementary school children with ASD at recess. Teaching initiations has been suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 21 publications
3
49
0
3
Order By: Relevance
“…Of these 35 studies, 18 studies targeted a pivotal skill. Seventeen studies targeted self-initiations (e.g., Koegel et al 2012) and one study targeted motivation (Koegel et al 2010b). Across studies, a variety of untargeted skills or collateral changes were measured.…”
Section: Dependent Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these 35 studies, 18 studies targeted a pivotal skill. Seventeen studies targeted self-initiations (e.g., Koegel et al 2012) and one study targeted motivation (Koegel et al 2010b). Across studies, a variety of untargeted skills or collateral changes were measured.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…For example, Smith et al used the Social Responsiveness Scale (Constantino and Gruber 2005) to identify changes in autism symptoms. Three studies evaluated collateral changes in affect as a result of PRT using rating scales (Koegel et al 2012;Robinson 2011;Vismara and Lyons 2007). Two studies evaluated collateral changes in cognitive functioning as result of PRT Steiner et al 2013), N total number of participants in study, PDD-NOS pervasive developmental disorder not otherwise specified, NR not reported, FU follow-up, Gen generalization, SV social validity, IOA inter-observer agreement, TF treatment fidelity using the Mullen Scales of Early Learning or the MerrillPalmer-Revised Scales of Development (Mullen 1995;Roid and Sampers 2004).…”
Section: Dependent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence-based practices (EBPs) are the basis on which teachers and other service providers are required to design educational programs for learners with autism spectrum dis-orders (ASD).Thus, an increasing number of students with disabilities, including those with ASD, are being educated in inclusive settings around the world (Koegel et al 2012). In the course of recent decades, there has been a common and widespread drive by international governments towards inclusion as a model for education.…”
Section: Introductionmentioning
confidence: 99%